Meta‐Liquid Crystals: Tunable Meta‐Liquid Crystals (Adv. Mater. 8/2016). Issue 8 (February 2016) - Liu, Mingkai; Fan, Kebin; Padilla, Willie; Powell, David A.; Zhang, Xin; Shadrivov, Ilya V.
Abstract : Meta‐liquid crystals (MLCs), a novel form of tunable 3D metamaterials, are proposed and demonstrated by M. Liu and co‐workers as described on page 1553. The response of the MLCs can be switched by changing the orientation of the meta‐molecules with a biased electric field. In comparison to conventional liquid crystals, there is considerable freedom to prescribe the electromagnetic properties through the judicious design of the meta‐atom geometry.